Computed-tomography-guided biopsy in suspected spondylodiscitis: Single-center experience including 201 biopsy procedures - Özmen, Derya (Orthop Rev (Pavia), 2019)
Our propose is to evaluate CT-guided biopsies in suspected spondylodiscitis with respect to puncture site, microbiology findings, histopathology findings and impact on antibiotic therapy. 86 CT-guided spine interventions in suspected spondylodiscitis comprising 201 biopsy procedures were analyzed. Medical records of all patients were screened for microbiology and histopathology reports as well as date, duration and kind of antibiotic therapy. Statistical analyses included calculation of Chi(2)-tests and logistic regression analyses. Locations of biopsies were intervertebral disc (48.3%), paravertebral soft-tissue (38.3%) and vertebral body (10.9%). Positive microbiological findings were found altogether in 33.8% of cases, positive histopathological findings in 53.6%. Significant associations between positive microbiological findings, positive histopathological findings and antibiotic therapy, respectively, were found. Location of biopsies did not significantly influence rate of positive findings. From the variables age, white blood cell count, serum creatinine and puncture site, none were found to be an independent predictor for a positive microbiological result. We concluded that CT-guided biopsy of intervertebral disc and paravertebral soft tissue yields positive microbiologic findings in a significant proportion of cases. Puncture site is not associated with positive results of microbiology or histopathology.